Resistance band training after triamcinolone acetonide injection for subacromial bursitis: A randomized clinical trial - Pengfei Zhu; Bokai Liao; Zhengchao Wang; Zhenxing Sun; Yang Wei; Yu Cai (Medical Journals Sweden, 2021)
Objective: To investigate the effect of progressive resistance training using resistance (elastic) bands on subacromial bursitis following triamcinolone acetonide injection. Design: Randomized clinical trial. Patients: A total of 68 patients with subacromial bursitis were randomized to a triamcinolone acetonide group or a triamcinolone acetonide plus resistance band training group. Methods: Visual analogue scale, Constant scores, range of motion, proprioception, and muscle strength were evaluated at pretreatment and at 3, 12 and 24 weeks' follow-up. Re-treatment ratio was calculated at one-year follow-up. Results: At 3 and 12 weeks, both the triamcinolone acetonide group and triamcinolone acetonide plus resistance band training group showed a significant improvement in Visual analogue scale score, Constant score, range of motion, proprioception and muscle strength. Although the scores in the triamcinolone acetonide group had not increased at 24 weeks compared with baseline, the scores in the triamcinolone acetonide plus resistance band training group showed continued improvement at 24 weeks. A lower proportion of patients in the triamcinolone acetonide plus resistance band training bands group than in the triamcinolone acetonide group had received re-treatment at one-year follow-up (12.1% vs 82.9%). Conclusion: Progressive resistance training with resistance (elastic) bands has the advantages of extending the benefits of corticosteroid injection and maintaining long-term effects on shoulder function in patients with subacromial bursitis.